A study on the numerical analysis for OFI in a narrow rectangular flow channel. (January 2021) - Park, Jong-Pil; Park, Cheol; Park, Suki
Highlights: The flow channel of a plate fuel can be place in asymmetric heating condition. OFI is analyzed for a narrow rectangular channel with the different heat fluxes. OFI point tend to move as the ratio of heat fluxes at two sides. Abstract: The prediction of the OFI is important for open pool type research reactors since the flow instability may lead to a premature CHF and cause a fuel failure. Hence, we implemented two-phase models on the commercial CFD code using user-defined functions to simulate a subcooled boiling and predict OFI flow at low pressure conditions. The capability of this CFD code with the two-phase models was assessed by the W&F experiment, which is for OFI in a rectangular flow channel with the same heat fluxes on both sides. Numerical assessments for OFI in a narrow rectangular channel with different heat fluxes on both sides was also simulated considering the practical operating conditions of typical open pool type research reactors with plate type fuels. Simulation results show that a commercial CFD code with the models implemented in this study properly predict the OFI at low pressure in a narrow rectangular channel.